PAR Reduction in Space-Time Coded OFDM via Modified Active Constellation Extension - Pradeep Kumara T. G., Amila; Moh Lim, Sim (2008)
High peak-to-average ratio (PAR) is one of the main problems in Orthogonal Frequency Division Multiplexing (OFDM) systems. This problem becomes more complicated when Space-time codes (STC) are employed as any PAR reduction method should not destroy the relationships among STC encoded OFDM symbols. There are existing PAR reduction methods for STC-OFDM systems. However, these methods do not provide sufficient performance of PAR reduction without complex receivers. In this paper, we propose Modified Active Constellation Extension (Modified ACE) method for STC encoded OFDM systems to provide 3.5dB of PAR improvement at a 10(-3) complementary cumulative density function (CCDF) of PAR. Most importantly, Modified ACE does not require any complex receivers or side information.